(untitled) (Bangladesh Pharmaceutical Journal, 2019)
We studied the metal contaminations as well as antimicrobial and antioxidant activities of five medicinal species: Berberis lyceum (Sumbal), Datura stramonium (Joz-e-masel), Semicarpous anacardium (Bhalawa), Fumaria indica (Shahtara) and Gymnema sylvestre (Gurmar) using atomic absorption spectrophotometry and agar-well diffusion method against E. coli and S. aureus and ABTS+● decolorization assay. We found that the contamination levels of K, Ca, Mg, and Ni are above the standard permissible limits and should be monitored. B. lyceum has been found to possess highest antimicrobial activities against both strains. Besides B. lyceum, D. stramonium, S. anacardium and F. indica have shown promising antioxidant activities. Phytochemical investigations are required to isolate antimicrobial and antioxidant compounds from these medicinal plants. Bangladesh Pharmaceutical Journal 22(1): 7-12, 2019